Un historiador argentino en viaje. Juan Alvarez, entre el intelectual y el turista - Oscar R. Videla (Nuevo mundo - Mundos Nuevos, 2010)
One of the most ignored aspects of Juan Alvarez's work (for sure oneof the most praised and less historiographically analyzed Argentinehistorian) are his travel writings. Having been published in the daily press over more than ten years, a vast series of travel accounts by the restless historian from Rosario can be found among them. Just as most of the intellectuals of his generation, Alvarez was a fervent traveller (he made several trips to Europe, the United States, Canada or to the distant New Zealand) but, unlike them, his itineraries were not always that common (Tahiti, India and almost all of South America).In this paper we are interested in exploring the views through which Alvarez, the traveller, observes, experiences and narrates some of these destinations. In particular, we want to inquire into two dimensions. One of them, the most classical among the intellectuals of his age, the view of the scholar devoted to external realities as a mirror and/or in contrast to his own, either as an inventory or a warning about the national future. The other dimension, the other view which slips in through his writings, is more contemporary, less substantial and more relaxed, it belongs to the traveller in search of leisure, to the tourist who tours and observes places (normally with a semiorganized exoticism), laters howing to his readers an inventory which is springs from admiration rather than social or political reflection.